The twelve dogs of christmas eaudiobook - Rosenfelt, David (Andy Carpenter, 2016)
"Grover Gardner's narration of Rosenfelt's whodunits is what good audiobooks are all about, and this newest performance is a prime example. Gardner's delightful portrayal of defense lawyer Andy Carpenter continues to be fresh, allowing listeners to glimpse Andy's soft heart and humor, despite his often cynical view of the world." — AudioFile Magazine on Outfoxed "Gardner's breezy, slightly sarcastic delivery is just what's needed for Rosenfelt's breezy, slightly sarcastic mysteries featuring multimillionaire New Jersey lawyer Andy Carpenter." — Publishers Weekly on Play Dead Defense lawyer Andy Carpenter usually tries to avoid taking on new cases at all costs. But this time, he's happy—eager, even—to take the case that's just come his way. Andy's long-time friend Martha "Pups" Boyer takes in stray puppies that the local dog rescue center can't handle, raises them until they're old enough to adopt, and then finds good homes for them. Not everyone admires the work Pups does as much as Andy does, however. With Christmas just around the corner, one of Pups's neighbors has just reported Pups to the city for having more than the legal number of pets in her home under the local zoning laws. Andy happily takes Pups's case, and he feels confident in a positive outcome. Who could punish someone for rescuing puppies, after all, especially at Christmastime? But things get a lot more complicated when Randy Hennessey, the neighbor who registered the complaint against Pups, turns up dead. Pups had loudly and publicly threatened Hennessey after he filed his complaint, and Pups was also the one to find his body. All the evidence seems to point to Pups as the killer, and suddenly Andy has a murder case on his hands. He doesn't believe Pups could be guilty, but as he starts digging deeper into the truth behind Hennessey's murder, Andy may find himself facing a killer more dangerous than he ever imagined. With his trademark wit, larger-than-life characters, and clever plotting, David Rosenfelt delivers another gripping mystery.